Characteristics and Clinical Profile of Vitiligo Patients in Dermatology and Venereology Outpatient Clinic Unit at Dr. Soetomo General Academic Hospital Surabaya - Arifin Saiboo, Alvian; Indramaya, Diah Mira; Hidayati, Afif Nurul; Damayanti; rahmadewi; Utomo, Budi; Eliza, Frizka; Cita Rosita Sigit Prakoeswa (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Vitiligo is a depigmentation disorder characterized by the progressive loss of melanocytes from the epidermis and hair follicles. Vitiligo affects all age groups and is defined by acquired, idiopathic, progressive, different-sized, circumscribed, milky white depigmentation. Characteristics and clinical patterns of vitiligo will also help to understand the pathogenesis of the disease. Purpose: The aim of this study is to evaluate the characteristics profile and clinical features of vitiligo patients. Methods: The research material was taken from the medical record of vitiligo patients in the Division of Cosmetics Outpatient Clinic Dermatovenerelogy Dr. Soetomo General Hospital Surabaya from 2018-2020. Result: This study was obtained by a number of new vitiligo patients 115 (0.3%) of the total number of new outpatient clinic visits of Dermatovenereology Dr. Soetomo General Hospital Surabaya. The majority of the gender is female (53.9%), late adolescence (26.96%), students (25.22%), and the onset of vitiligo 1-5 years (30.43%). The most common risk factors were idiopathic (51.3%) and clinical types are non-segmental vitiligo (53.04%). Conclusion: Vitiligo predominantly affects in females with active age groups of 17-25 years old, and students.